Recognition of depression, anxiety, and alcohol abuse in a Chinese rural sample: a cross-sectional study. Issue 1 (December 2016) - Yu, Yu; Hu, Mi; Liu, Zi-wei; Liu, Hui-ming; Yang, Joyce; Zhou, Liang; Xiao, Shui-yuan
Abstract Background Under-utilization of mental health services is a global health issue. Recognition of mental disorders, as the first step to seeking help from professional sources, has been well studied in developed countries, yet little is known about the situation in rural areas of developing countries like China. The purpose of the study is to understand the recognition of depression, anxiety, and alcohol abuse and its predictive factors in a Chinese rural sample Methods Face-to-face interviews were conducted on a representative rural adult sample in a cross-sectional study in China (N  = 2052). Respondents were presented with three vignettes depicting depression, anxiety and alcohol abuse and asked to label the disorder and its cause to assess their recognition of the three mental disorders. They also completed the Patient Health Questionnaire (PHQ-9), the Generalized Anxiety Disorder Scale (GAD-7), and the Alcohol Use Disorders Identification Test (AUDIT) to assess their current mental health status. Results The alcohol abuse vignette was more frequently attributed as a mental problem than the depression vignette and anxiety vignette. The correct labeling rate was 16.1 % in the depression vignette, 15.5 % in the anxiety vignette, and 58.2 % in the alcohol vignette. Higher education is the common and also strongest factor positively predicting the recognition of all three vignettes. Beyond that, being female is an independent predictor of correct recognition of alcohol abuse, while recognition of depression and anxiety were positively predicted by younger age. Conclusions Lower recognition of depression and anxiety as compared to alcohol abuse confirms the importance and need to increase the public's awareness and knowledge about common mental disorders. Recognition of common mental disorders could be improved through general public campaign and education, while paying attention to the unique predictive factors for each specific disorder and implement targeted intervention.